Pengaruh Substitusi Tepung Kedelai dan Tepung Ikan Teri terhadap Kadar Protein dan Kalsium Crackers - Enik Sulistyowati; Wiwik Wijaningsih; Sri Noor Mintarsih (Poltekkes Kemenkes Semarang, 2015)
The study objective to determine the effect of substitution of soy flourl and flour anchovy in various proportions to protein and calcium crackers and acceptability in children under five. A preliminary study was conducted to determine two of the five most preferred panelists. Substitution is used soy flour and flour anchovy 5%, 10%, 15%, 20%, 25%. Having obtained two composition that produces the most preferred crackers followed by the main research to acceptability of children under five and analysis of protein and calcium. The difference in the preference panelists on crackers analyzed by Friedman test. Effect of soy flour and flour anchovy substitution on protein and calcium crackers used ANOVA. Differences acceptance crackers in toodler was analyzed with chi square test. The results showed crackers substitution soy flour and flour anchovy 5% and 10% favored panelists and toddlers. The energy of crackers substitution 5% is 421.97 Calories and substitution 10% was 429.59 Calories. The protein of crackers substitution 5% is 10.97 grams and the substitution of 10% is 17.1 grams. The calcium of crackers substitution 5% is 25,07mg and substitution of 10% was 37.6 mg. Substitution of flour soy and flour anchovy 5% and 10% increase protein and Calcium crackers. Making crackres should be substituted soy flour and flour anchovy 10%.